181 SIBSHIP POSITION IN THE MASCULINIZATION OF ARM AND HAND BONE RATIOS IN FEMALE PATIENTS WITH TYPE 2 DIABETES. Issue 1 (1st January 2007) - Sayed, D.; Wilson, K.; Martin, J. T.
Abstract : Previous data from our laboratory and from others have demonstrated a link between sibship position and sexual differentiation in human males, with homosexuals having a higher sibship position and more older brothers than heterosexual males. Whether this relationship is due to sibship-dependent differences in androgen exposure during development is not known. There is also evidence that females with type 2 diabetes are born later in the sibship and also have higher plasma androgen levels, but, again, it is not known if these two factors are related. In this study the relationship between sibship position and potential markers of androgen exposure during development was analyzed. Participants in the study included 745 patients, staff, or visitors to six hospitals or clinics in Southern California. Data were collected on health and family history by questionnaire and eight anatomic traits in the lower arms and hands were measured. Female diabetics were found to have a significantly higher birth order than control females ( p = .0220). Female diabetics were also found to have significantly higher ulna length to stature ratios than female controls ( p = .0002) and were nearly identical to male ratios. However, increased birth order in female diabetics was not associated with higher ulna length to stature ratios. Increased number of older brothers in female diabetics was also not associated with increased ulna length to stature ratios. Larger ulna length:stature ratios in female diabetics may possibly be attributed to increased testosterone levels in these women since this ratio is also higher in males compared with females. Although there is no evidence that sibship factors affect the ulna length:stature ratio, it is possible that sibship factors influence other sexually dimorphic or androgen-dependent bone ratios, which have yet to be analyzed. A larger sample size of female diabetics may be necessary to elucidate the relationship between birth order and masculinization of bone ratios among diabetics.